Copyright Protection in Philosophical View as A Natural Right - Krisna Mukti Pradana; Bayu Abdillah; Dominikus Rato; Fendy Setiawan (Rechtenstudent, 2024)
Copyright is intellectual property that needs to be protected in order to encourage respect for creative works and prevent copyright infringement. The aim of this research is to analyze the form of legal protection for copyright as a natural right from a philosophical perspective. The research method used is normative juridical with a philosophy approach. The results of this research are that the philosophy of copyright recognition refers to two theories, namely based on natural law theory and utilitarianism theory. Based on natural law theory, copyright is natural right after the creative work is completed, so the protection is automatic, there is no need for registration or enrollment. Recognition of copyright to creators as a moral right is adopted by Indonesia and France. Meanwhile, based on the Utilitarian theory, recognition of copyright in works, as an economic right, which requires registration, so that recognition and protection is given by the state through law, this theory is followed by America, England and Australia.